Point of care, bone marrow mononuclear cell therapy in ischemic heart failure patients personalized for cell potency: 12-month feasibility results from CardiAMP heart failure roll-in cohort. (1st March 2021) - Raval, Amish N.; Johnston, Peter V.; Duckers, Henricus J.; Cook, Thomas D.; Traverse, Jay H.; Altman, Peter A.; Dhingra, Ravi; Hematti, Peiman; Borrello, Ivan; Anderson, R. David; Pepine, Carl J.
Abstract: Aim: Heart failure following myocardial infarction (MI) is a potentially lethal problem with a staggering incidence. The CardiAMP Heart Failure trial represents the first attempt to personalize marrow-derived cell-based therapy to individuals with cell characteristics associated with beneficial responses in prior trials. Before the initiation of the randomized pivotal trial, an open-label "roll-in cohort" was completed to ensure the feasibility of the protocol's procedures. Methods: Patients with chronic post-MI heart failure (NYHA class II-III) receiving stable, guideline-directed medical therapy with a left ventricular ejection fraction between 20 and 40% were eligible. Two weeks prior to treatment, a ~ 5 mL bone marrow aspiration was performed to examine "cell potency". On treatment day, a 60 mL bone marrow aspiration, bone marrow mononuclear cell (BM MNC) enrichment and transendocardial injection of 200 million BM MNC's was performed in a single, point of care encounter. Patients were then followed to assess clinical outcomes. Results: The cell potency small volume bone marrow aspirate, the 60 mL bone marrow aspirate, and transendocardial injections were well tolerated in 10 patients enrolled. There were no serious adverse events related to bone marrow aspiration or cell delivery. Improvement in 6-min walk distance was observed at 6 months (+47.8 m, P  = 0.01) and trended to improvement at 12 months (+46.4, P  = 0.06). Similarly, trends to improved NYHA heart failure functional class, quality of life, left ventricular ejection fraction and recruitment of previously akinetic left ventricular wall segments were observed. Conclusion: All CardiAMP HF protocol procedures were feasible and well tolerated. Favorable functional, echo and quality of life trends suggest this approach may offer promise for patients with post MI heart failure. The randomized CardiAMP Heart Failure pivotal trial is underway to confirm the efficacy of this approach. Clinical trial registration: https://clinicaltrials.gov/ct2/show/NCT02438306 Highlights: CardiAMP HF trial will test personalized cell therapy for heart failure patients. A 10 patient, open-label, roll-in cohort was performed for protocol feasibility. Per protocol procedures were feasible and well-tolerated in all roll-in patients. No significant serious adverse safety responses were observed. Efficacy trends were observed for functional, quality of life and echo parameters.